2019
DOI: 10.1016/j.jcmg.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Dilated Cardiomyopathy Related to the Extent, Location, and Pattern of Late Gadolinium Enhancement

Abstract: In DCM, the presence of septal LGE is associated with a large increase in the risk of death and SCD events, even when the extent is small. SCD risk is greatest with concomitant septal and free-wall LGE. The incremental value of LGE extent beyond small amounts and LGE pattern is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
171
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(197 citation statements)
references
References 21 publications
14
171
2
10
Order By: Relevance
“…remarkably similar incidence of LGE at NIDCM presentation (35%) to the vast literature on established NIDCM (12)(13)(14). This essentially represents "pre-diagnosis" fibrosis highlighting the significant duration of pre-clinical disease in NIDCM and providing impetus for study of It is increasingly recognised that myocardial scar induced re-entry arrhythmias make up the majority of VA in the cardiomyopathic heart (26,27).…”
Section: Accepted Manuscriptmentioning
confidence: 69%
See 1 more Smart Citation
“…remarkably similar incidence of LGE at NIDCM presentation (35%) to the vast literature on established NIDCM (12)(13)(14). This essentially represents "pre-diagnosis" fibrosis highlighting the significant duration of pre-clinical disease in NIDCM and providing impetus for study of It is increasingly recognised that myocardial scar induced re-entry arrhythmias make up the majority of VA in the cardiomyopathic heart (26,27).…”
Section: Accepted Manuscriptmentioning
confidence: 69%
“…In the largest study to date, Halliday et al reported a remarkably similar prevalence of LGE of 34.3% (14). This study of 874 patients with NIDCM demonstrated that patients with myocardial fibrosis on LGE are more likely to have significant VA events and death (14). The same group prospectively studied patients with NIDCM with an LVEF 40%…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Two studies were then excluded because of repetition of cohort, 7,15 and a further 16 studies were excluded because of lack of raw data or otherwise ineligible comparison of study design with selection criteria. Finally, seven studies 8,9,[12][13][14]16,17 enrolling 1827 patients were included for the meta-analysis. Figure 1 provides further details regarding the identification and selection process.…”
Section: Study Inclusion and Exclusionmentioning
confidence: 99%
“…A recent observational study49 suggests that among patients with DCM and LVEF<35%, ICD implantation was associated with a reduction in mortality only among those with LGE. An even more recent publication following 874 patients over a median of 4.9 years highlighted the increased risk of septal and lateral mid-wall LGE but indicated that the incremental value of LGE extent beyond the presence of LGE was small 50. Randomised trials are needed to assess whether ICD provides prognostic advantage to patients with DCM and severe LVSD but no LGE; if no benefit is found and only those with LVEF<35% and LGE were given an ICD, the number needed to treat to save one life would be significantly reduced.…”
Section: Future Directionsmentioning
confidence: 99%